2016
DOI: 10.1038/srep24454
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Aided Diagnosis with Deep Learning Architecture: Applications to Breast Lesions in US Images and Pulmonary Nodules in CT Scans

Abstract: This paper performs a comprehensive study on the deep-learning-based computer-aided diagnosis (CADx) for the differential diagnosis of benign and malignant nodules/lesions by avoiding the potential errors caused by inaccurate image processing results (e.g., boundary segmentation), as well as the classification bias resulting from a less robust feature set, as involved in most conventional CADx algorithms. Specifically, the stacked denoising auto-encoder (SDAE) is exploited on the two CADx applications for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
337
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 568 publications
(365 citation statements)
references
References 45 publications
1
337
0
7
Order By: Relevance
“…The most basic approach is to fine tune with a small set of labeled data after extracting relevant features from unlabeled data via unsupervised learning. Cheng et al obtained a performance better than the current CADx system by pretraining a stacked denoising autoencoder (SDAE) to determine the malignancy of a lesion from chest CT images [13].…”
Section: Lesion Detection and Classificationmentioning
confidence: 99%
“…The most basic approach is to fine tune with a small set of labeled data after extracting relevant features from unlabeled data via unsupervised learning. Cheng et al obtained a performance better than the current CADx system by pretraining a stacked denoising autoencoder (SDAE) to determine the malignancy of a lesion from chest CT images [13].…”
Section: Lesion Detection and Classificationmentioning
confidence: 99%
“…Furthermore, we plan to use a deep learning approach to find discriminant features and combine them with handcrafted features (e.g., local patterns from LQP operators). Although several studies [22][23][24][25][26][27][28][29] have investigated the use of deep learning in breast density classification, to the best of our knowledge, the separation was only based on two-or three-class classification (none of the deep learning based approaches has been applied to four-class classification). In fact, no study has been conducted combining non-handcrafted and handcrafted features in breast density classification.…”
Section: Future Workmentioning
confidence: 99%
“…Qui et al [27] proposed three pairs of convolution-max-pooling layers that contain 20, 10, and five feature maps to predict short-term breast cancer risk and achieved 71.4%. Using a deeper network approach, Cheng et al [28] proposed an eight multi-layer deep learning algorithm to employ three pairs of convolution-max-pooling layers for mammographic masses classification and reported AUC of 0.81. In a similar problem domain (mass classification), Jiao et al [29] used CNN and a decision mechanism along with intensity information and reported an average of 95% accuracy on different sizes of datasets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, when building a disease diagnosis model, patient's various information such as symptoms, tests as well as diagnosis should be extracted and fed into the model [14,15]. However, Formal studies usually focused on recognizing a single type of clinical entities from clinical texts.…”
Section: Introductionmentioning
confidence: 99%